MENGANALISIS KETERGANTUNGAN MAHASISWA DALAM PENGGUNAAN DOMPET DIGITAL (STUDY PRODI PPKN) - Rospianita, Aninda; M Salman Hanapi; Auliya Rahmawati; Cinta Nurhidayah; Hayatunnisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify how the use of digital wallets among PPKn FKIP UNRAM students. This study uses a qualitative descriptive method, with data collection through interviews, observations, and documentation. The subjects of the study were PPKn FKIP UNRAM students. The results of the study show that the level of digital wallet use among students is quite high and the types of digital wallet applications that are predominantly used are the DANA and ShoppePay applications because of the ease and speed of making payments, many promotions, cashback, and other attractive offers, this creates a sense of urgency to immediately take advantage of the opportunity, thus worsening the tendency for impulse shopping. The use of digital wallets by students has a significant impact on their shopping habits, which indirectly also affects the traditional retail industry. and also the risk of identity theft on digital wallets is minimal because the digital wallet application itself is equipped with security features that have been guaranteed by OJK, available security features, such as PIN, fingerprint, and facial authentication. These features make digital wallets more difficult to access by unauthorized parties.